Preparation and spectroscopic studies of ZnO incorporated PVA nanocomposite films. (2022) - Satheesh Goud, J.; Srinivas, Ch.; Narsimlu, N.
Abstract: Incorporation of zinc oxide nanoparticles (ZnO NPs) into a polyvinyl alcohol (PVA) base matrix forms its nanocomposite films. Their morphological, spectroscopic, and thermal properties were studied using X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Ultraviolet–visible Spectrophotometry (UV–vis) spectroscopy, and Differential Scanning Calorimetry (DSC) methods. In this investigation, various weight percentages (0, 2, 4, 6, and 8 wt%) of ZnO NPs were incorporated into PVA using the solution casting method. According to XRD studies, the ZnO nanoparticles' original structure was preserved in the Polyvinyl alcohol–Zinc oxide nanocomposite (PVA-ZnO NC) films, and the crystallinity of the PVA-ZnO NC films was increased. The SEM images confirmed that the ZnO NPs were uniformly spread on the surface film. The UV–visible investigations were carried out, and the values of the refractive index, Urbach energy, direct bandgap, and indirect bandgap were assessed. The loading of 0 to 8 wt% of ZnO NPs in the PVA matrix resulted in a significant change in direct bandgap from 6.16 eV to 5.61 eV, indirect bandgap from 5.89 eV to 5.24 eV, Urbach energy from 0.428 eV to 0.538 eV, linear refractive index from 1.64 to 2.67, and extinction coefficient from 0.00016 to 0.00065. These results showed that the spectroscopic properties of PVA-ZnO NC films were modified considerably with small loadings of ZnO NPs in the PVA matrix due to cross-linking formation between the nanoparticles and the polymer. The DSC results demonstrated that increasing the weight percentage of ZnO NPs had no effect on the glass transition temperature or melting point of the composite films.